2009
DOI: 10.2208/jsceje.65.564
|View full text |Cite
|
Sign up to set email alerts
|

Influence That Seasonal Variation in State of Include Concrete Water Exerts on Characteristic of Carbonation Process of Underground Structure

Abstract: 5 正会員 東洋大学教授 理工学部都市環境デザイン学科(〒350-8585 埼玉県川越市鯨井2100) 本研究では,地中コンクリート構造物の中性化進行特性について,通信土木構造物を例に評価した.そ の結果,地中コンクリート構造物は季節変化に伴う緩やかな乾湿繰り返しを受け,その含水状態は表面含 水率で把握することができ,乾燥によって地中構造物は一般構造物と同様に中性化が進むことがわかった. この事象を供試体による透気性試験を行い,表面含水率によって大きく変化することを確認した.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Adopted mean value shown in Table is used to predict the end of the initiation stage for each group. Although recent research reported that water on the concrete surface affects the progress of carbonation, this study neglects such local water actions for the sake of simplicity.…”
Section: System Detailsmentioning
confidence: 99%
“…Adopted mean value shown in Table is used to predict the end of the initiation stage for each group. Although recent research reported that water on the concrete surface affects the progress of carbonation, this study neglects such local water actions for the sake of simplicity.…”
Section: System Detailsmentioning
confidence: 99%